Rainbowlicious / Amira Aisyah Jamari ... [et al.] - Jamari, Amira Aisyah; Awg Bakari, Dayang Azleena; Adam, Hashimah; Arifin, Juada; Abdul Sanih, Siti Masturah (2014)
This business is based on partnership where it is consists of five(5) members which hold important positions in the company such as General Manager, Administration Manager, Marketing Manager, Operational Manager and Financial Manager. The business capital is amounted to RM 30,000 where the total contribution of each member is RM 6000 and the rest RM 45,000 from SME Bank loan. Our company name is Rainbowlicious. Our business is focused in Kota Kinabalu Sabah. We have registered our company on 15th January 2015. Our business start to move on 10thJanuary 2015 and this date are same as our company date of commencement. Our business is operating at the kiosk which is at Centre Point Shopping Mall, I st floor Kota Kinabalu. Our business is providing the services of planning, preparing and making much kind of booths and buffet for any event such as birthday party, wedding day, baby shower day and many more. Rainbowlicious will offering their customer with many package services of candy buffet with our customer own ideas of theme or customize by us to attract their guest besides enjoying the variety kind of desserts and sweetooth which is also provide in our services. At the same time, we want to create a wonderful time together with their friends, family and loves. We also want to help people that want a unique and memorable event for them. These are also the reasons why we choose this business. With the loan given as the support from the SME Bank, we are hoping and wishing to make Rainbowlicious able to achieve outstanding demand from customer. Our vision is to be the only company is the best in preparing and making much kind of booths and buffet for any event. This will be realized by the full cooperation and efforts among the partners to promote company. Based on the vision above, we are venturing into food industry. Rainbowlicious has the potential of being a profitable business if it is done in modem way with large scale and systematically managed.